Saberes docentes como mediadores didáticos e conceituais na formação inicial de professores de Matemática - Ledoux, Maria Lídia Paula (2016)
This is a qualitative research that brings, as investigation focus, the teacher knowledge of the Mathematics Teachers Graduates of the Federal University of Pará, Campus of Castanhal. These teachers develop their teaching practices in public schools in the micro-region of Salgado, which was the context where it was done a field research in order to investigate the graduating teachers' knowledge to understand how these can be understood as didactic and conceptual mediators in the initial training of mathematics teachers. Through the observations in the field of research, I developed an architecture to conceptualize three dimensions of knowledge: Teacher Personal Knowledge; Training Knowledge and Knowledge of Teaching Practice, in order to understand how the concept of knowledge is interrelated in processes that require values, beliefs and cultural practices of a given society. Eight qualified teachers in mathematics were taken as part of this research. The instruments to establish the information were questionnaire, interview and journaling field. As analysis methodology, I made use of the Discursive Textual Analysis that is part of the production and reconstruction movements of the investigated realities. From the analysis, five categories emerged that originated the units of meaning: Initial Teacher Education: training practice-based content; Shortcoming on Teacher Training: Practice Commitment in the classroom; Knowledge of the specific knowledge: Senses and Meanings; Teaching Practice: learning to be a teacher in the practice of the classroom, and Teachers knowledge: initial training mediators. The analysis of these units is in line with the thesis defended by me that the practical experiences experienced by the mathematics teachers graduates are able to promote the development of teaching knowledge. In addition, they can be used as basis to provide the didactic and conceptual mediation in training process in order to minimize the shortcoming on teacher Training and form different teachers to work in Basic Education. The results point to the proposition that it is possible to train teachers differently, considering the presence of elements such as teaching mediated by research; differentiated teaching methodologies; pedagogical residence throughout the training and constant revision and reformulation on the processes of the PPC of the course. This research reveals notes that focus on initial training of mathematics teachers, organized in processes that require procedural actions, considering: Promote in initial training, procedures in which the class actions are close to the educational reality as an essential practice to the teacher in training; Integrate specific knowledge and teaching skills, in order to promote the basis of understanding needed to provide those teachers, the feeling of belonging to their profession; Insert teaching, research and extension as articulators elements and promoters of a significant learning in the initial training of mathematics teachers. In this proposition, I manifest the understanding that a differentiated formation takes place from the opening to dialogue, to the challenges, to the innovations and to the necessary changes to the training of teachers able to understand the importance of their social role and their relationship with the world.